The attorneys' fees and the in court in the CPC of 2015 (Revista do Tribunal Regional Federal da 3ª Região, 2016)
In this brief essay, I intend to provide interested readers with some reflections on the 2015 CPC's discipline of attorneys' fees, with an emphasis on public procedural law. The summary of the previous issues is sufficient not only to give an overview but also to suggest various questions about the system of legal fees which, with the entry into force of the new Code of Civil Procedure, will deserve more detailed attention from the doctrine and case law. Not only the scholar, but also the practitioner of "public procedural law", has the special onus of raising these various issues in order to make it possible to crystallize a doctrinal and jurisprudential understanding that is in line with what the 2015 CPC clearly intends in what has taken it the furthest away from the 1973 CPC: the frequent and derisory condemnations of succumbent fees in cases involving the Public Treasury, in the terms suggested by the literality of the aforementioned § 4 of art. 20 of the current Code. In fact, it is correct to understand, in view of § 3 of art. 85 of the 2015 CPC, that there will no longer be any normative space to give grounds to decisions as frequent as the mistaken ones that deny the setting of attorneys' fees, under the 1973 CPC system - such as those I illustratively listed in footnote 5 above - without observing the percentage limits of § 3 of art. 20, arguing that the rule of § 4 is specific to any and all legal proceedings involving the Public Treasury.
Keywords: CPC 2015; attorney's fees; public power in court